Alleviation of cadmium (Cd) toxicity and minimizing its uptake in wheat (Triticum aestivum) by using organic carbon sources in Cd-spiked soil. (October 2018) - Rehman, Muhammad Zia ur; Rizwan, Muhammad; Hussain, Amjad; Saqib, Muhammad; Ali, Shafaqat; Sohail, Muhammad Irfan; Shafiq, Mahnoor; Hafeez, Farhan
Abstract: Cadmium (Cd)-contamination of agricultural soils has been receiving attention worldwide due to its entry into food crops such as wheat ( Triticum aestivum L.). Little is known regarding the use of organic carbon (OC) sources in alleviating Cd toxicity in cereals. The current experiment was aimed to study the effects of different OC sources on the Cd accumulation by wheat. A pot study was conducted to determine the effects of rice husk biochar (RHB), farmyard manure (FYM), and lignite (LT) either alone or in combination on crop growth, Cd bioavailability and health risk assessment. The results proved that the application of OC sources like RHB, FYM, and LT either alone or in combination were highly effective in enhancing the wheat growth and yield as well as in minimizing the phyto-available fraction of Cd and its transfer to edible tissue of wheat. The RHB was the most efficient source in enhancing the plant growth and reducing the Cd concentration in wheat tissues. RHB increased grain yield by 91% and decreased Cd concentration in shoot, roots, grains, and bioavailable fraction of Cd by 67, 69, 62.5, and 74% than control, respectively. The RHB reduced the daily Cd uptake and health risk index in adults in comparison to control. Overall, where un-amended soil resulted in diminished plant productivity, the application of other OC sources also significantly proved their potential to enhance the dry weight and grain yield, suggesting that these OC sources may be used aiming to minimize the Cd concentration in crops. However, there is still a need to explore the potential of different OC sources in combination with other frequently available amendments for their large scale implementation in metal-contaminated soils. Graphical abstract: Highlights: Rice husk biochar (RHB) was more effective in increasing wheat growth attributes and biomass. RHB was highly effective in reducing cadmium (Cd) concentration in grains of wheat. All amendments influenced the Cd translocation factor, tolerance index and harvest index. Each amendment significantly decreased the AB-DTPA extractable Cd in soil. Abstract : Rice husk biochar was more effective in increasing plant growth and yield and reducing Cd in wheat grains than other commonly available amendments.